Evaluation of Serum parathyroid hormone level measurement in total thyroidectomy patients (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Postoperative hypoparathyroidism is a common complication after total thyroidectomy. It is necessary to diagnose hypoparathyroidism immediately after total thyroidectomy for minimizing complications.Objective: The objective of this study was to measure and to evaluate the serum parathyroid hormone level in total thyroidectomy patients.Methods: This prospective observational study was carried out in the Department of Clinical Pathology in collaboration with Department of Surgery & Department of Otolaryngology of BSMMU and Department of Otolaryngology of DMCH, Dhaka, during the period of September 2010 to August 2011.Results: Total 65 patients were studied irrespective of age and sex. Decreased serum PTH was found in 9 cases and normal parathyroid hormone was found in 56 cases. Male was 16.0% and female was 84.0%. Females were predominant. The incidence of hypoparathyroidism was 41.5%. Asymptomatic hypoparathyroidism was found in 8 and symptomatic hypoparathyroidism was found in 1 cases. Decreased serum PTH was developed mostly in malignant thyroid diseases. In relation to preoperative PTH values, intraoperative PTH levels were lower from 5.48% to 90.0%, (mean±SD in percentage is 65.3±16.7, p=.001) which is significant in paired t test. The mean difference of intraoperative (20 minutes after total thyroidectomy), parathyroid hormone levels were statistically significant (p